Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To prove that the statement is true for all natural numbers \( n \), we will use the principle of mathematical induction.
### Step 1: Base Case
First, we need to confirm the base case. Let's consider \( n = 1 \).
For \( n = 1 \), the number of dots, \( d(1) \), is 1.
So, \( d(1) = 1 \).
### Step 2: Inductive Hypothesis
Assume that the statement is true for \( n = k \). That means,
[tex]\[ d(k) = \frac{k \times (k + 1)}{2} \][/tex]
### Step 3: Inductive Step
We need to show that if the statement holds for \( n = k \), then it also holds for \( n = k + 1 \).
We know that by the assumption for \( n = k \):
[tex]\[ d(k) = \frac{k \times (k + 1)}{2} \][/tex]
We need to prove:
[tex]\[ d(k+1) = d(k) + (k + 1) \][/tex]
Let's compute \( d(k+1) \) using the inductive hypothesis:
[tex]\[ d(k+1) = d(k) + (k + 1) = \frac{k \times (k + 1)}{2} + (k + 1) \][/tex]
Combine the terms over a common denominator:
[tex]\[ d(k+1) = \frac{k \times (k + 1)}{2} + \frac{2 \times (k + 1)}{2} = \frac{k \times (k + 1) + 2 \times (k + 1)}{2} = \frac{(k + 2) \times (k + 1)}{2} = \frac{(k + 1) \times (k + 2)}{2} \][/tex]
Since we have shown:
[tex]\[ d(k+1) = \frac{(k+1) \times (k+2)}{2} \][/tex]
This matches the pattern for triangular numbers, confirming our inductive step.
### Conclusion
By proving the base case for \( n = 1 \) and using the inductive step to show that \( d(k) \) being true implies \( d(k+1) \) is also true, we have proven by induction that the statement is true for all natural numbers \( n \).
Hence, the formula holds as demonstrated by the inductive proof. For instance, if \( k = 5 \):
[tex]\[ d(5) = \frac{5 \times (5 + 1)}{2} = 15 \][/tex]
[tex]\[ d(6) = d(5) + 6 = 15 + 6 = 21 \][/tex]
Thus,
[tex]\[ d(5) = 15 \quad \text{and} \quad d(6) = 21 \][/tex]
### Step 1: Base Case
First, we need to confirm the base case. Let's consider \( n = 1 \).
For \( n = 1 \), the number of dots, \( d(1) \), is 1.
So, \( d(1) = 1 \).
### Step 2: Inductive Hypothesis
Assume that the statement is true for \( n = k \). That means,
[tex]\[ d(k) = \frac{k \times (k + 1)}{2} \][/tex]
### Step 3: Inductive Step
We need to show that if the statement holds for \( n = k \), then it also holds for \( n = k + 1 \).
We know that by the assumption for \( n = k \):
[tex]\[ d(k) = \frac{k \times (k + 1)}{2} \][/tex]
We need to prove:
[tex]\[ d(k+1) = d(k) + (k + 1) \][/tex]
Let's compute \( d(k+1) \) using the inductive hypothesis:
[tex]\[ d(k+1) = d(k) + (k + 1) = \frac{k \times (k + 1)}{2} + (k + 1) \][/tex]
Combine the terms over a common denominator:
[tex]\[ d(k+1) = \frac{k \times (k + 1)}{2} + \frac{2 \times (k + 1)}{2} = \frac{k \times (k + 1) + 2 \times (k + 1)}{2} = \frac{(k + 2) \times (k + 1)}{2} = \frac{(k + 1) \times (k + 2)}{2} \][/tex]
Since we have shown:
[tex]\[ d(k+1) = \frac{(k+1) \times (k+2)}{2} \][/tex]
This matches the pattern for triangular numbers, confirming our inductive step.
### Conclusion
By proving the base case for \( n = 1 \) and using the inductive step to show that \( d(k) \) being true implies \( d(k+1) \) is also true, we have proven by induction that the statement is true for all natural numbers \( n \).
Hence, the formula holds as demonstrated by the inductive proof. For instance, if \( k = 5 \):
[tex]\[ d(5) = \frac{5 \times (5 + 1)}{2} = 15 \][/tex]
[tex]\[ d(6) = d(5) + 6 = 15 + 6 = 21 \][/tex]
Thus,
[tex]\[ d(5) = 15 \quad \text{and} \quad d(6) = 21 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.